If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -8y = 2y + -8 Reorder the terms: 2 + -8y = -8 + 2y Solving 2 + -8y = -8 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 2 + -8y + -2y = -8 + 2y + -2y Combine like terms: -8y + -2y = -10y 2 + -10y = -8 + 2y + -2y Combine like terms: 2y + -2y = 0 2 + -10y = -8 + 0 2 + -10y = -8 Add '-2' to each side of the equation. 2 + -2 + -10y = -8 + -2 Combine like terms: 2 + -2 = 0 0 + -10y = -8 + -2 -10y = -8 + -2 Combine like terms: -8 + -2 = -10 -10y = -10 Divide each side by '-10'. y = 1 Simplifying y = 1
| a^2+b^2+c^2+4abc=4 | | 12=6(4y+1)-2(7y+7) | | 35n/2n | | f(x)=2x+x^2+3(4x)+17*f(7) | | f(x)=2x+x^2+3(4x)+17*7 | | 8(5u-3)-4(7u+4)=32 | | 4.5x+7-9.5x=2 | | 7(7u-8)=5(u-9)+385 | | 6x-2x-1=5+9(-63) | | -5y^2-27+48y=0 | | 0.3x+15.5=x-7.74 | | -6(x+1)-8=-4(x-3) | | 2(2x-2.2)=9x-4.4 | | -0.2x+2.91=-0.4x+1.11 | | -5w-(7/3)=(1/3w)-(3/4) | | 4x(x)+25x=0 | | (3/5u)-(4/3)=(-6/5u)=3 | | x^4+sqrt(17)*x^2-17=0 | | 7x-6=8x-9 | | 25/36-2/5(-1/3) | | 5(x+1.01)=4x | | (x+y)dx+(x+y)dy=0 | | -1/2x^2-7/2x-5 | | 1/2x^2-7/2x-50 | | (1/3w)-(4/3)=(-7/4w)-1 | | 5/6^2-2/5(-1/3) | | -1/2x^2-7/2x-50 | | 200x-0.05=600x+0.59 | | (-3/4v)-(3/4)=2v-(1/3) | | 3.1x-91=1.2x+4 | | (1/2)-(1/5y)=(-1/3) | | 6.1=10x+1.3 |